Prinsip Good Governance dan Akuntabilitas Fiskal: Bukti Empiris dari Pengelolaan Anggaran Kabupaten Sumenep - Rafdiansyah, Moh. Rayhan; Ronaboyd, Irfa (JURNAL USM LAW REVIEW, 2025)
This study analyzes the implementation of good governance principles in managing the Regional Revenue and Expenditure Budget (APBD) of Sumenep Regency in 2023. The research is based on Sumenep’s condition as an archipelagic region with fiscal limitations and geographical challenges that affect financial management effectiveness. The study underscores the need to balance fiscal decentralization with the principles of transparency, accountability, public participation, effectiveness, efficiency, and the rule of law. Using an empirical approach and a descriptive-analytical design, it combines interview data from the Regional House of Representatives (DPRD) and community figures with analyses of the Budget Realization Report, audit results from the Audit Board of Indonesia (BPK), and relevant regulations. Results show that transparency improved through the PPID portal but remains limited by publication timeliness and data format; accountability is still administrative due to dominant routine spending (83.9%) over capital expenditure (16.1%); public participation is mainly formal through Musrenbang; fiscal effectiveness is low because of high logistics costs and stagnant HDI (68.61); while the rule of law emphasizes procedural compliance without strong enforcement and anti-corruption control. The study’s novelty lies in its comprehensive empirical mapping of the five good governance principles in archipelagic regional financial management.   Penelitian ini bertujuan menganalisis penerapan prinsip good governance dalam pengelolaan APBD Kabupaten Sumenep Tahun 2023. Latar belakang penelitian ini berangkat dari kondisi Kabupaten Sumenep sebagai wilayah kepulauan dengan keterbatasan fiskal dan tantangan geografis yang berdampak pada efektivitas tata kelola keuangan daerah. Urgensi penelitian terletak pada perlunya memastikan desentralisasi fiskal berjalan seimbang dengan prinsip transparansi, akuntabilitas, partisipasi publik, efektivitas dan efisiensi, sertasupremasi hukum. Menggunakan pendekatan empiris dan rancangan deskriptif-analitis, penelitian ini mengombinasikan data wawancara dengan DPRD dan tokoh masyarakat serta analisis terhadap Laporan Realisasi APBD, hasil audit BPK, dan regulasi terkait. Hasil menunjukkan bahwa transparansi meningkat melalui portal PPID, namun masih terkendala ketepatan publikasi dan format data; akuntabilitas belum substantif karena dominasi belanja rutin 83,9 persen dibanding belanja modal 16,1 persen; partisipasi publik bersifat formal melalui Musrenbang; efektivitas fiskal rendah karena biaya logistik tinggi dan IPM stagnan 68,61; sedangkan supremasi hukum masih menekankan kepatuhan prosedural tanpa penguatan penegakan dan kontrol antikorupsi. Kebaruan penelitian ini terletak pada pemetaan empiris komprehensif terhadap lima prinsip good governance dalam konteks keuangan daerah kepulauan.